Pengaruh Leader Member Exchange Dan Employee Engagement Terhadap Kinerja Pegawai Dengan Pemoderasi Budaya Organisasi (Studi pada Sekretariat Dewan Perwakilan Rakyat Daerah Kota Semarang) - Rina Dewi; Widhy Setyowati (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to examine and analyze the effect of Leader Member Exchange and Employee Engagement on Performance with Organizational Culture moderation. The number of samples as many as 97 respondents obtained from the sampling technique of the sensus method. Technical data analysis includes validity test through factor analysis, reliability test and continued with multiple linear regression test. Four hypotheses were proposed in this study. The results of the statistical test stated that all indicators were valid and reliable. Furthermore, in the regression test, it is found that Leader Member Exchange and Employee Engagement are proven to contribute to explaining performance. In the f test, it is confirmed that Leader Member Exchange and Employee Engagement have a simultaneous effect on performance. The t-test proves that there is a positive and significant influence of Leader Member Exchange on performance as well as a positive and significant influence of Employee Engagement on Performance. Furthermore, in the moderation test, it was found that Organizational Culture was able to become a Moderating Variable and was reinforcing on the Influence of Leader Member Exchange on Performance and Organizational Culture was able to be a Moderating Variable and was reinforcing on the influence of Employee Engagement on Performance.